Smart Tour Travel Purwokerto's Service Quality Improvement Strategy for Customer Satisfaction - Nurdin, Ali; Qalban, Anas Azhimi (Journal Sensi: Strategic of Education in Information System, 2025)
This research discusses strategies for improving the quality of Smart Tour Travel Purwokerto services in an effort to increase customer satisfaction. The research method used is a qualitative approach with a case study design. Data was collected through interviews, direct observation, and analysis of internal company documents. The research results show that the main factors in increasing customer satisfaction include service speed, staff privacy, travel comfort, and transportation safety. The strategies implemented include employee training to increase professionalism, development of an application-based ordering system, and rejuvenation of the vehicle fleet. Survey results showed a significant increase in customer satisfaction after this strategy was implemented. Improving service quality not only has an impact on customer loyalty, but also strengthens the company's competitiveness in the travel industry. Therefore, innovation and continuous improvement are key in maintaining customer satisfaction and business desires.